Preparation and Characterization of Chitosan/Feldspar Biohybrid as an Adsorbent: Optimization of Adsorption Process via Response Surface Modeling. (23rd January 2014) - Yazdani, Maryam; Bahrami, Hajir; Arami, Mokhtar
Abstract : Chitosan/feldspar biobased beads were synthesized, characterized, and tested for the removal of Acid Black 1 dye from aquatic phases. A four-factor central composite design (CCD) accompanied by response surface modeling (RSM) and optimization was used to optimize the dye adsorption by the adsorbent (chitosan/feldspar composite) in 31 different batch experiments. Independent variables of temperature, pH, initial dye concentration, and adsorbent dose were used to change to coded values. To anticipate the responses, a quadratic model was applied. Analysis of variance (ANOVA) tested the significance of the process factors and their interactions. The adequacy of the model was investigated by the correlation between experimental and predicted data of the adsorption and the calculation of prediction errors. The results showed that the predicted maximum adsorption amount of 21.63 mg/g under the optimum conditions (pH 3, temperature 15°C, initial dye concentration 125 mg/L, and dose 0.2 g/50 mL) was close to the experimental value of 19.85 mg/g. In addition, the results of adsorption behaviors of the dye illustrated that the adsorption process followed the Langmuir isotherm model and the pseudo-second-order kinetic model. Langmuir sorption capacity was found to be 17.86 mg/g. Besides, thermodynamic parameters were evaluated and revealed that the adsorption process was exothermic and favourable.